Gestão do processo assistencial e de processamento de Banco de Leite Humano com foco na melhoria da qualidade - Torrezan, Ana Carolina (2010)
Human milk is considered the nutrient most suitable for the newborn so the Ministry of Health recommends exclusive breastfeeding until six months of life. With the policy of encouraging, supporting and promoting breastfeeding among other strategies emerged the Human Milk Bank (HMB), which through its history, currently form the Brazilian Network of Human Milk Banks Network (HMB-BR). One function of the HMB is the processing of human milk, donated voluntarily initiating the capture of the donor and is meant to distribution of pasteurized human milk to newborns, especially those who remain in the NICU. For this process to occur with safety and quality activities must meet rigorous standards and current legislation. Because of the importance and relevance of this theme study aimed to develop a proposal for process management and assistance activities of the processing of human milk with a HMB focus on improvement quality. Data were collected by observing activities in HMB, during the period of one month and in the archives of the Human Milk Bank Network site HMB-BR between the years 2005 and 2009. Then these activities were grouped in welfare activities and activities of processing and quality control and then measured. The Methodological Process Management was used to guide this study in directions to achieve the objectives. The strategies were used to describe the organizational model HMB using the graphical, flowchart, mapping and modeling activities by offering a clear and systematic in their operation. The results have demonstrated the importance of process management for service quality management by providing constant monitoring, achieving an efficient and effective continuous quality HMB.